Proof of concept testing of an integrated dry injection system for SO sub x /NO sub x control - Helfritch, D.J.; Bortz, S.J. (Research-Cottrell, Inc., Somerville, NJ (United States). Environmental Services and Technologies Div.); Beittel, R. (Riley Stoker Corp., Worcester, MA (United States)) (Research-Cottrell, Inc., Somerville, NJ (United States). Environmental Services and Technologies Div., 1989)
The objectives of the subscale test program were designed to provide sorbent and additive selection guidance, and, in so doing, supply answers to the questions posed in the preceding section. The objectives are: Identify the best commercial hydrate sorbent and the best enhanced hydrate sorbent from a list of nine types, based upon S0{sub 2} removal at Ca/S=2. Determine the relative effectiveness of sodium sesquicarbonate versus sodium bicarbonate for S0{sub 2} and NOsub x control over the temperature range of 200degreesF--400degreesF. Identify the best NOsub 2 suppressing additive among the group of ammonia, urea, and activated carbon.